The Motion Verbs with Particles and Prepositions: Semantic Analyses - Budiana, Haris (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
THE MOTION VERBS WITH PARTICLES AND PREPOSITIONS